2020
DOI: 10.12982/cmujns.2021.019
|View full text |Cite
|
Sign up to set email alerts
|

Insight on the In Silico Study and Biological Activity Assay of Chalcone-Based 1, 5-Benzothiazepines as Potential Inhibitor for Breast Cancer MCF7

Abstract: In silico study was performed to twelve 1,5-benzothiazepine chalcone derivatives with the protein target from the crystallographic structure modeling of the enzyme tyrosine kinase. The objective of this study is to execute and to estimate the biological activity of chalcone-based 1,5-benzothiazepine derivatives as potential inhibitors for breast cancer MCF7. To get insight into potential anticancer activities, molecular docking, molecular dynamic and ADME prediction were performed. Docking results reported tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
(6 reference statements)
0
9
0
1
Order By: Relevance
“…The lowest binding free energy is the main parameter to determine the binding stability between ligand and protein. This also showed that the ligand interaction with the receptor was more stable due to the decreased binding free energy value [12]. In addition, selection of the best poses for docking results was also carried out using root mean square deviation (RMSD).…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest binding free energy is the main parameter to determine the binding stability between ligand and protein. This also showed that the ligand interaction with the receptor was more stable due to the decreased binding free energy value [12]. In addition, selection of the best poses for docking results was also carried out using root mean square deviation (RMSD).…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Thus, compound 3 predicted to be active compounds. The lowest binding free energy and lowest RMSD value of this molecule, which may presumably cause compound 3 to has better binding affinity compare to other compounds [14]. Superimposition is binding method that showed several residues play an important role in determine binding interactions for all ligands.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…A grid box of the protein structure was then achieved with a grid spacing of 1 Å, dimensions of 31 x 25 x 35 points along the x, y, and z-axes, and centered on the protein active site. Docking was performed using Autodock vina software packages (Frimayanti et al, 2021).…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Based on our previous research, the in vitro assay revealed that one of 1,5-benzothiazepine derivatives i.e. MA9 exhibited an enhanced biological activity compared to doxorubicin (the common agent for treatment of breast cancer 11 ).…”
Section: Introductionmentioning
confidence: 99%